LITOSTRATIGRAPHIC AND SEDIMENTOLOGICAL SIGNIFICANTS OF DEEPENING MARINE SEDIMENTS OF THE SAMBIPITU FORMATION GUNUNG KIDUL RESIDENCE, YOGYAKARTA - Surono Surono; Asep Permana (Marine Geological Institute of Indonesia, 2011)
Sambipitu Formation in the Southern Mountains plays an important role due to its stratigraphic position, between syn-volcanism and post- volcanism periods. The formation widely distributes along the southern slope of the Baturagung Mountains, Gunung Kidul Residence, Yogyakarta Province. Stratigraphically, the Sambipitu Formation is conformably underlain by dominated unit of volcanic breccias of the Nglanggran Formation, and conformably overlain by dominated unit of marl of the Oyo Formation. Based on detail section along the river of Ngalang, the Sambipitu Formation can be divided into Lower and Upper Members. The Lower Member is dominated by sandstone and siltstone, which is alternated by breccias. The Upper Member is dominated by siltstone and mudstone, which is intercalated by sandstone, marl and conglomerate. The Lower Member was deposited on an environment influenced by tidal current, which was highly affected by gravity flows of volcanic material. This deposition environment was getting deeper to be an inner shelf, where the Upper Member was deposited. Furthermore, based on Rock-eval pyrolysis, TOC value of the Sambipitu Formation ranges from 0.08% to 0.43%, whilst the PY (potential yield) value less than 0.15 mg HC/g rock. Thus, on the basis of those two parameters, the Sambipitu Formation is included into oil prone source rock potential of poor category. Moreover, Tmax value of the Sambipitu Formation ranges from 226°C - 335°C, with the HI (hydrogen Index) value varies from 0 – 12. It indicates that this formation contains kerogen Type III. Therefore, the organic thermal maturation based on plotting of Tmax vs HI, this formation falls into an immature category. Key word: Lithostratigraphy, volcanic material, tidal flat, inner shelf, and Sambipitu Formation. Formasi Sambipitu memegang peran penting karena posisi stratigrafinya yang terletak diantara perioda volkanisme dan pasca volkanisme. Formasi ini tersebar luas di lereng selatan Pegunungan Baturagung, Kabupaten Gunung Kidul, Provinsi Daerah Istimewa Yogyakarta. Formasi Sambipitu menindih selaras Formasi Nglanggran dan ditindih selaras oleh Formasi Oyo. Berdasarkan penampang stratigrafi rinci sepanjang Sungai Ngalang, Formasi Sambipitu dapat dibagi menjadi: Anggota Bawah dan Anggota Atas. Anggota Bawah didominasi oleh perselingan batupasir dan batulanau, dengan sisipani breksi gunung api. Sedangkan Anggota Atas didominasi oleh batulanau dan batulumpur dengan sisipan batupasir dan konglomerat. Anggota Bawah diendapkan di lingkungan paparan pasang-surut yang dipengaruhi oleh pengendapan material gunung api. Paparan pasang-surut itu semakin dalam menjadi paparan dalam dimana diendapkan Anggota Atas. Berdasarkan analisis Rock-eval pirolisis, nilai kandungan karbon total (TOC) serpih Formasi Sambipitu berkisar 0,08% – 0,43%, sedangkan Potential yield (kandungan cairan hidrokarbon) kurang dari 0,15 mg HC/g batuan. Berdasarkan dua parameter tersebut diatas, formasi tersebut termasuk kedalam kategori oil prone source rock, dengan kategori buruk (poor). Formasi Sambipitu mempunyai nilai temperatur maksimum (Tmax) antara 226°C - 335°C, dengan nilai HI (Hydrogen Index) kurang dari 12, menunjukkan formasi ini memiliki kerogen tipe III. Berdasarkan diagram temperatur maksimum (Tmax) terhadap nilai indeks hidrogen (HI) bahan organik, kematangan organik dari formasi ini termasuk ke dalam tingkat belum matang. Kata kunci: Litostratigrafi, material volkanik, paparan pasang-surut, paparan dalam, dan Formasi Sambipitu.